1999
DOI: 10.1152/jappl.1999.87.3.1172
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 sensitivity of porcine coronary arteries is reduced by exercise training and is gender dependent

Abstract: We tested the hypothesis that exercise training reduces the sensitivity of coronary smooth muscle to endothelin-1 (ET-1), with the adaptation being greater in male than in female miniature swine. The efficacy of training was similar in males and females. Cumulative ET-1 contractile responses of coronary branches and left circumflex artery were significantly shifted to the right in exercise-trained (Ex) males but not in Ex females. Analyses of the excitatory concentration causing a 50% response (EC(50)) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
2
41
0
1
Order By: Relevance
“…We also found no sex difference in endothelin concentration required to attain similar levels of preconstriction. This finding is in contrast to those of others using larger porcine coronary arteries (14,24) and supports heterogeneity in physiological and pharmacological responses in vessels of different sizes (4,15,20).…”
Section: Discussionsupporting
confidence: 68%
“…We also found no sex difference in endothelin concentration required to attain similar levels of preconstriction. This finding is in contrast to those of others using larger porcine coronary arteries (14,24) and supports heterogeneity in physiological and pharmacological responses in vessels of different sizes (4,15,20).…”
Section: Discussionsupporting
confidence: 68%
“…Exercise training-induced alterations to the coronary vasculature include increases in smooth muscle cell K ϩ channel activity that are related to L-type voltage-gated Ca 2ϩ channels and subsarcolemmal Ca 2ϩ cycling (6). Previously, Jones et al (23) demonstrated exercise training-induced reductions in coronary artery sensitivity to ET-1 in male miniature swine was mediated, in part, by an increase in smooth muscle K ϩ channel activation. These studies support the idea maintenance of smooth muscle cell Ca 2ϩ -sensitive I K ϩ following exercise training in the present study may underlie the preservation of normal coronary vascular function in HF-TR animals.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of exercise on coronary vascular function are well known (6,15,30). Training-induced alterations to the coronary vasculature include both increases in smooth muscle cell K ϩ channel activity (6) and reductions in coronary artery sensitivity to ET-1 mediated, in part, by an increase in smooth muscle cell K ϩ channel activation (23). In nonpathological models, exercise has also been shown to impact coronary smooth muscle cell electrophysiological contributions to coronary basal tone, including Ca 2ϩ -activated K ϩ currents (4,5).…”
mentioning
confidence: 99%
“…This observation is in line with recent animal studies that report exercise training in healthy animals to result in a downregulation of the ET pathway. For example, a decrease in receptor sensitivity to ET-1 in pig coronary arteries 32 and rat aortic and cerebellar vessels 33 is reported after exercise training. However, the reversal of the contribution of ET-1 to leg vascular tone in our study was not complete, suggesting that ET-1 may not be the only factor in vascular adaptation to SCI or, alternatively, that the training period did not last long enough.…”
Section: February 2007mentioning
confidence: 99%